DNA identification of kayu kuning (yellow-fruited moonseed) from East Kalimantan, Indonesia - Riski Sulistiarini (Pharmaciana, 2022)
Kalimantan is an island with an abundance of kayu Kuning (yellow-fruited moonseed). Kayu kuning is used for three different plant species, namely Arcangelisia flava (L.) Merr., Fibraurea tinctoria Lour., and Coscinium fenestratum (Gaertn.) Colebr. Therefore, it creates confusion and may cause improper use. It has properties such as anti-diabetic, antiplasmodial, antidiarrheal, hepatitis, and antidote. The study uses the DNA barcode technique to identify kayu kuning (yellow-fruited moonseed) from East Kalimantan, Indonesia. The genomic DNA of kayu kuning (yellow-fruited moonseed) was extracted, and ITS primers were used for identification using polymerase chain reaction (PCR). It was compared with Arcangelisia flava, Fibraurea tinctoria, and Coscinium fenestratum as a phylogenetic tree. DNA sequence alignment of ITS and phylogenetic reconstruction revealed that kayu kuning (yellow-fruited moonseed) from East Kalimantan was closely related to A. flava. The kayu kuning (yellow-fruited moonseed) had 94.16% of sequence similarity with A. flava according to the ITS1 barcode.